The Effect of Foreign Direct Investment on Economic Growth: Evidence from Iraq - Shlair Abdulkhaleq; Zhiar Abdulqadir (International Journal of Social Sciences & Educational Studies, 2017)
Inflows of Foreign direct investment (FDI) have been recently perceived as an important determinant of Iraq economic growth. This paper studies the effect that the increasing levels of FDI inflows have on levels of economic growth in Iraq. An Ordinary Least Square (OLS) regression model was employed to analyze the relationship between two variables. Two regression equations were constructed. One predicted the logarithm of GDP levels measured at current prices/billions of US$ and the other predicted levels of per capita GDP at PPP measured at current prices/billions of US$ during the period 2004-2015. In both of equations, the dependent variable was the levels of FDI as net inflows to Iraq’s balance of payment in current US$, and it turned to be statistically significant in predicting levels of economic growth in Iraq.